Students’ Perceptions Toward the Features of E-learning UNP in English Learning - Sri Rejeki; M. Affandi Arianto (Journal of English Language Teaching, 2022)
During Covid-19, the learning system has changed to online. Many universities use various online learning platforms in order to get learning activities run as expected. Therefore, Universitas Negeri Padang implemented the use of E-learning. This study aims to see students' perceptions toward the features of E-learning UNP in the Paragraph Writing course. The research design used is descriptive quantitative with a questionnaire instrument consisting of 30 items. Then, English Education Students registered in academic year 2021 became the population in this study and 36 of them became the sample. The researcher found that students Perceived Easy of access with a mean of 3.27, Perceived Usefulness of 3.42, Perceived Instruction Delivery of 3.40. Additionally, they also gave positive attitudes such as feeling happy with a mean of 3.14, not bored 2.91 and like with a mean 3.23. It means, the students gave a positive perception of the use of E-learning features, especially the feature of delivering material in the Paragraph Writing class.